A direct contact pig influenza challenge model for assessing protective efficacy of monoclonal antibodies - McNee, Adam; Vanover, Daryll; Rijal, Pramila; Paudyal, Basudev; Lean, Fabian Z. X.; MacLoughlin, Ronan; Núñez, Alejandro; Townsend, Alain; Santangelo, Philip J.; Tchilian, Elma (Frontiers in Immunology, 2023)
Monoclonal antibodies (mAbs) can be used to complement immunization for therapy of influenza virus infection. We have established the pig, a natural large animal host for influenza A, with many physiological, immunological, and anatomical similarities to humans, as an appropriate model for testing mAbs. We have evaluated the protective efficacy of the strongly neutralizing human antihemagglutinin mAb, 2-12C in the pig influenza model. Intravenous administration of recombinant 2-12C reduced virus load and lung pathology but did not prevent virus nasal shedding and therefore by implication transmission. This may be because the pigs were directly infected intranasally with a high dose of H1N1pdm09 virus. To address this, we developed a contact challenge model in which the animals were given 2-12C and one day later co-housed with donor pigs previously infected intranasally with H1N1pdm09. 2-12C pre-treatment completely prevented infection. We also administered a lower dose of 2-12C by aerosol to the respiratory tract, but this did not prevent shedding in the direct challenge model, although it abolished lung infection. We propose that the direct contact challenge model of pig influenza may be useful for evaluating candidate mAbs and emerging delivery platforms prior to clinical trials.